Compton Camera and Prompt Gamma Ray Timing: Two Methods for In Vivo Range Assessment in Proton Therapy - Hueso-González, Fernando; Fiedler, Fine; Golnik, Christian; Kormoll, Thomas; Pausch, Guntram; Petzoldt, Johannes; Römer, Katja E.; Enghardt, Wolfgang (Frontiers in Oncology, 2016)
Proton beams are promising means for treating tumours. Such charged particles stop at a defined depth, where the ionization density is maximum. As the dose deposit beyond this distal edge is very low, proton therapy minimises the damage to normal tissue compared to photon therapy. Nevertheless, inherent range uncertainties cast doubts on the irradiation of tumours close to organs at risk and lead to the application of conservative safety margins. This constrains significantly the potential benefits of protons over photons. In this context, several research groups are developing experimental tools for range verification based on the detection of prompt gammas, a nuclear by-product of the proton irradiation. At OncoRay and Helmholtz-Zentrum Dresden-Rossendorf, detector components have been characterised in realistic radiation environments as a step towards a clinical Compton camera. Corresponding experimental methods and results obtained during the ENTERVISION training network are reviewed. On the other hand, a novel method based on timing spectroscopy has been proposed as an alternative to collimated imaging systems. The first tests of the timing method at a clinical proton accelerator are summarised, its applicability in a clinical environment for challenging the current safety margins is assessed, and the factors limiting its precision are discussed.